Identification and selection of animal health and food safety-related risk factors to be included in the Canadian Food Inspection Agency's risk assessment model for livestock feed mills. (March 2021) - Rhouma, Mohamed; Lachapelle, Virginie; Comeau, Geneviève; Quessy, Sylvain; Zanabria, Romina; Provost, France; Italiano, Catherine; Holley, Rick; Smillie, John; Brockhoff, Egan; Bosch, My-Lien; Collins, Stephanie; et al.
Abstract: The safety of livestock feed is recognized worldwide as a prerequisite for the protection of animal and human health. In this context, the Canadian Food Inspection Agency is developing an Establishment-based Risk Assessment model for livestock feed mills (ERA-Feed Mill) to assist in the allocation of inspection resources based on feed safety risk. The objectives of the present study were to identify and select animal health and food safety-related risk factors along with their assessment criteria, pertaining to Canadian feed mill practices, to be included in the ERA-Feed Mill model. To do so, a review of the scientific literature and consultations with feed experts were conducted. A final list of 34 risk factors was generated, 21 identified from the scientific literature and 13 from feed expert advice. Risk factors were grouped into three clusters: inherent risk factors, mitigation factors and compliance factors for which 4, 10 and 20 factors were identified, respectively. Criteria for quantitatively assessing each risk factor were defined based on common practices found in the Canadian feed industry. These findings contributed to the initial steps of the CFIA's ERA-Feed Mill model development. By assessing the feed safety risk factors related to feed mills in Canada, this tool will help inform the CFIA on the level of oversight required to manage these risks, and will contribute to the production and maintenance of healthy livestock and the production of safe food. Highlights: A risk assessment model for commercial and on-farm feed mills is being developed. This model covers both animal health and food safety risks related to feed mills. 34 risk factors were generated based on scientific literature and expert advice. Assessment criteria were defined based on practices found in the feed industry. Results will support the allocation of inspection resources based on risk.